2014
DOI: 10.1007/s11356-013-2088-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of water environmental capacity—a case study on the western areas of Taihu Lake in Jiangsu Province, China

Abstract: Currently, the poor water quality in Taihu Lake is a major problem in China, so pollution control in the upstream areas has become a government priority. In Jiangsu Province, pollution emissions around the western areas of Taihu Lake, including Changzhou Municipality and Yixing City, need to be highly restricted, and calculating the water environmental capacity is important if pollution is to be reduced. In this study, 19 control units in these areas were established, and a 0-D mathematical model was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Figure 8 also shows that river discharge has some helpful effect on DO by renewing water in the hypoxia section with more oxygenated upstream freshwater. At very low discharges, residence time of water bodies is longer, water renewal is lower and the environmental capacity of nutrients in water reduces [ 42 ]. Oxygen consumption increases due to degradation of the organic carbon and ammonium by continuous input from Guangming River and Baima River.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 also shows that river discharge has some helpful effect on DO by renewing water in the hypoxia section with more oxygenated upstream freshwater. At very low discharges, residence time of water bodies is longer, water renewal is lower and the environmental capacity of nutrients in water reduces [ 42 ]. Oxygen consumption increases due to degradation of the organic carbon and ammonium by continuous input from Guangming River and Baima River.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant studies [59,60,61,62] have shown that the control of the total amount of pollutants in water is crucial for the management of the water environment. For a multiple outlets lake, the outlets are often the river channels of the city.…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, the province had a serious water pollution incident [ 37 ]. With its recent rapid development, the province currently emits a huge amount of wastewater [ 38 , 39 ]. Considering this, the method we proposed allocated a lower emission permit to this province.…”
Section: Resultsmentioning
confidence: 99%